2020
DOI: 10.3390/en13030662
|View full text |Cite
|
Sign up to set email alerts
|

Energy Efficiency of a Heat Pump System: Case Study in Two Pig Houses

Abstract: This study describes a 70-day investigation of three identical groundwater heat pumps (GWHP) for heating two pig houses located on the same farm in West Germany. Two of the three GWHPs were installed in a piglet-rearing barn, the third in a farrowing barn. All three heat pumps were fed from the same extraction well. The aim of this study was firstly the empirical performance measurement of the GWHP systems and secondly the energetic evaluation of the systems on barn level by calculating the coefficient of perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…It was reported that the single loop vertical GHP system (known as the direct heat exchange system) can efficiently transfer heat from the ground to the source building and the fan coil unit (FCU) of the GHP system can distribute that heat effectively due to the continuous motion [ 19 , 33 ]. In line with our findings, many scientists from different nations have explained the satisfactory heating capabilities of the GHP system for animal farms [ 6 , 19 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…It was reported that the single loop vertical GHP system (known as the direct heat exchange system) can efficiently transfer heat from the ground to the source building and the fan coil unit (FCU) of the GHP system can distribute that heat effectively due to the continuous motion [ 19 , 33 ]. In line with our findings, many scientists from different nations have explained the satisfactory heating capabilities of the GHP system for animal farms [ 6 , 19 , 35 , 36 ].…”
Section: Discussionsupporting
confidence: 91%
“…Pigs are more prone to heat stress in hot weather as they lack a proper panting system and a large deposit of subcutaneous fat under their skin [4]. In addition, Licharz et al [18] reported that pig housing must have access to a comfortable indoor temperature to comply with animal welfare legislation. The inside temperature of the AHP connected pig house remained at a lower level during the entire experiment.…”
Section: Discussionmentioning
confidence: 99%
“…The authors in [81] examined the effects of a heating system using a ground source heat pump for sustainable pig production and food security as a climate-friendly renewable energy source for a pig house. In addition, in [13] and [82], groundwater heat pumps in a pig house were considered for energy usage. Therefore, the main interest of farmers is to reduce the power consumption of energy-consuming entities while guaranteeing a comfortable rearing environment.…”
Section: Energy Analysis Of Pig House Using Digital Twinmentioning
confidence: 99%